INSATIABLE BEHAVIOR AS REFLECTED IN THE NECKLACE AND ITS CONNECTION TO SOCIAL MEDIA CONSUMERISM - Sastila Calista Sumbayak; Winarti Winarti (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2021)
The purpose of this study is to know insatiable behavior in the â€œNecklaceâ€ and its connection to social media consumerism The methodology of this study is a qualitative research method. The primary source of data is the â€œNecklaceâ€ short story, and the secondary source of the data is the dialogue, and action done by the main character. The result of this study shows that insatiable behaviors can be seen from the character Mme. Loisel. Her insatiable behaviors comes from her dissatisfaction about life. She's trying so hard to look like those who come from upper class society. Her jealousy on her friend, led her to the insatiable desire and her consumerism behavior. This behavior has connection to modern day's consumerism behavior.